2023
DOI: 10.3389/fevo.2023.1184582
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aboveground long-term low-dose ionizing radiation on soil microbial diversity and structure

Abstract: Studies investigating the diversity and structure of soil microbial systems in response to ionizing radiation are scarce. In particular, effects of long-term low-dose radiation is rarely studied because of its unique conditions. In this study, an area in Chengdu, China, which has been irradiated by the radionuclide thorium-232 for more than 10 years was investigated. Four groups of samples with absorbed dose rates ranging from 192.906 ± 5.05 to 910.964 ± 41.09 nGy/h were collected to analyze the compositional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Moreover, the abundance of Ectomycorrhizal fungi in the high group is 6 times that of the medium group, 13 times that of the low group, and 0 in the blank group. This indicates that under long-term ionizing radiation stress, plants transfer the main task of absorbing nutrients to symbiotic microorganisms mainly composed of Ectomycorrhizal fungi, resulting in significantly longer specific root length than that of the blank group, while the proportion of root dry matter is significantly lower than that of the blank group (Li et al, 2022;Cheng et al, 2023).…”
Section: Nitrogen Mineralization Effect Versus Symbiotic Microbial Ef...mentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the abundance of Ectomycorrhizal fungi in the high group is 6 times that of the medium group, 13 times that of the low group, and 0 in the blank group. This indicates that under long-term ionizing radiation stress, plants transfer the main task of absorbing nutrients to symbiotic microorganisms mainly composed of Ectomycorrhizal fungi, resulting in significantly longer specific root length than that of the blank group, while the proportion of root dry matter is significantly lower than that of the blank group (Li et al, 2022;Cheng et al, 2023).…”
Section: Nitrogen Mineralization Effect Versus Symbiotic Microbial Ef...mentioning
confidence: 95%
“…In general, plants usually enhance their resistance by stimulating root-driven microbial communities when facing environmental stress and the same is true when subjected to nuclear radiation stress ( Guesmi et al, 2022 ). Recent studies also indicated that under LLR conditions, plants tend to reduce aboveground biomass and invest more organic matter underground, thereby promoting the nutrient acquisition of the root-microbial system and improving the ecosystem’s adaptability to long-term nuclear radiation ( Li et al, 2022 ; Cheng et al, 2023 ). According to previous studies, there are mainly two ways for plants to promote the nutrient acquisition of the root-microbial system, namely the “nitrogen mineralization effect” and the “symbiotic microbial effect,” which will lead to changes in soil carbon and nitrogen cycling and enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
“…Here, another example of a radioactively exposed field is given. Chengdu in China was contaminated by low-dose 232 Th for more than 10 years, and Cheng et al (2023) [ 104 ] investigated the diversity and composition of microbes in 20 soil samples of which soil type, moisture, and pH did not differ. They found that fungal diversity was significantly reduced in irradiated soil groups (absorption dose rate of γ-rays: 630 nGy/h and 840 nGy/h) but not in bacterial diversity and that the compositions of both fungal and bacterial communities were affected.…”
Section: Soil Microbes and Soil Invertebratesmentioning
confidence: 99%
“…Bacteria could be more adaptive than fungi in general. In fact, proteobacteria exhibiting strong adaptability predominate in soil exposed to radiation and maintain the stability of the bacterial community [ 104 ]. These findings suggest that differences in radioadaptability could drive imbalances at any taxonomic level from domain to species in the soil ecosystem.…”
Section: Soil Microbes and Soil Invertebratesmentioning
confidence: 99%
See 1 more Smart Citation